Attention allocation and return co-movement: Evidence from repeated natural experiments - Huang, Shiyang; Huang, Yulin; Lin, Tse-Chun (Journal of Financial Economics, 2019)
We hypothesize that when investors pay less attention to financial markets, they rationally allocate relatively more attention to market-level information than to firm-specific information, leading to increases in stock return co-movements. Using large jackpot lotteries as exogenous shocks that attract investors’ attention away from the stock market, we find supportive evidence that stock returns co-move more with the market on large jackpot days. This effect is stronger for stocks preferred by retail investors and is not driven by gambling sentiment. We also find that stock returns are less sensitive to earnings surprises and co-move more with industries on large jackpot days.